The Influence Of Exposure To @Vina Muliana's Tiktok Content On The Level Of Job Searching Knowledge In Final Level Students Of Satya Wacana Christian University - Lakodjanga, Karmenita (Riviera Publishing, 2023)
Social media is an easy tool in this modern era where individuals and groups can quickly get information through pictures and videos containing the latest news or information regarding disasters, politics, education or work. Internet media is a medium that all levels of society can reach. With the internet, people can easily access what they want to know. Of the many social media that are frequently used, TikTok is one of the social networks and video platforms with the most fans from 2016 until now. TikTok is an application with many exciting features that interest people in watching every video displayed. In this journal, the author discusses the influence of exposure to @Vina Muliana's TikTok content where this research aims to determine the effect of exposure to @Vina Muliana's TikTok content on the level of job search knowledge among final-year students at Satya Wacana Christian University. Method: This research uses quantitative research. The sampling technique in this research used purposive sampling technique. Based on the research results, there is a strong influence between exposure to TikTok content and the level of job search knowledge among final students at Satya Wacana Christian University, with a figure of 0.714 or 0.714%. From all the results, @ Vina Muliana's TikTok content greatly influences job search knowledge among final-year students at Satya Wacana Christian University.